Monitoring of new and existing stainless-steel reinforced concrete structures by clad Distributed Optical Fiber Sensing - Distributed Optic Fibre Sensor data, Digital Image Correlation data and Actuator data. - Fernandez, Ignasi (Chalmers University of Technology, 2022)
The implementation of structural health monitoring systems in existing civil engineering structures could contribute to a safer and more resilient infrastructure as well as important savings. Due to their light weight, small size, and high resistance to the environment, distributed optical fibre sensors (DOFS) stand out as a very promising technology for damage detection and quantification in reinforced concrete structures. This dataset includes information of DOFS featuring an external polymeric cladding with rough surface, deployed in a stainless-steel reinforced concrete beam subjected to four-point bending. Several sensor positions, both embedded in the concrete and attached to the surface, are included in a multilayer configuration. The data of the sensors includes two series of test, first cyclic loading under service loads and lastly cyclic loading to failure. Additionally, data from Digital Image Correlation and the actuator recordings are included for cross-validation purposes.

The data included in this dataset basically consists in strain measurement of fibre optic sensor, i.e. BRUSens V9 cable, attached at different places on a Stainless-steel Reinforced Concrete Beam. The equipment to measure the strains of the sensor is an ODISI 6004 from Luna ink. which uses the Rayleight backscatter technology. In addition, Digital Image Correlation data is included offering mid-span deflections of the beam. The equipment used for the acquisition of the images and the corresponding displacement fields is a ARAMIS from GOM technologies, that features two 12 MP cameras.

The dataset is available in MatLab and GNU Octave/txt (https://www.gnu.org/software/octave/index) formats.

Digitala system för tillståndsbedömning av transportinfrastruktur bidrar till en säkrare, robustare och mer hållbar infrastruktur som i sin tur leder till minskade underhållskostnader. Ett digitalt system som har visat stor potential för skadedetektering i armerade betongkonstruktioner är distribuerade optiska fibersensorer (Distributed Optical Fibre Sensors). Systemet utmärker sig med en låg vikt, minimal storlek och hög robusthet. Detta dataset kommer från en fiber med en extern polymerbeklädnad grov yta, applicerad på en fyrpunktsbelastad betongbalk, armerad med rostfritt stål. Datasetet omfattar flera sensorpositioner, både ingjutna och ytmonterade, för två testserier: cyklisk belastning under brottgräns och cyklisk belastning till brott. Dessutom innehåller setet data från digital bildkorrelation (Digital Image Correlation) och lastgivare.

Datan består i grunden av töjningsmätningar från optiska fibrer, d.v.s en BRUSens V9 kabel, som är monterad på olika ställen längs en betongbalk armerad med rostfri armering. Utrustningen som mäter töjningarna i fibrerna är en ODISI 6004 från Luna ink som använder sig av Rayliegh tillbaka-spridning. Dessutom är data från en Digital Bildkorrelation inkluderat, som mäter nedböjningen i balkens mittspann. Utrustningen som används för bilderna och tillhörande nedböjningar är ARAMIS från GOM technologies, som använder två 12 MP kameror.

Datasetet är tillgängligt i MatLab och GNU octave/txt (https://www.gnu.org/software/octave/index) format.
Monitorering av nya och befintliga betongkonstruktioner med rostfri armering, utrustade med distribuerad fiberoptisk mätning - Data från distribuerad fiberoptisk mätning, Digital Bildkorrelation och Actuator.
Keywords: DOFS; DOFS; Distributed Optic Fibre Sensing; Distributed Optic Fibre Sensing; Construction Management; Byggprocess och förvaltning; Other Civil Engineering; Annan samhällsbyggnadsteknik